Gender differences in psychological morbidity, burnout, job stress and job satisfaction among Chinese neurologists: a national cross-sectional study. Issue 6 (3rd July 2017) - Pu, Juncai; Zhou, Xinyu; Zhu, Dan; Zhong, Xiaoni; Yang, Lining; Wang, Haiyang; Zhang, Yuqing; Fan, Songhua; Liu, Lanxiang; Xie, Peng; ,
Abstract: Women are an important part of the medical workforce, yet little is known about gender differences in psychological morbidity, burnout, job stress and job satisfaction among neurologists. This study assessed gender differences in a large national sample of Chinese neurologists. Multivariate analyses were performed to examine associations. A total of 5558 neurologists were included in the analysis. Compared with their male counterparts, female neurologists were generally younger; were less likely to be married or to have children; had higher levels of education; were in practice for a shorter period of time; were less likely to hold senior roles; and had lower incomes. Male and female neurologists worked similar hours and spent a similar number of nights on call. No gender differences were found in psychological morbidity, burnout, and high levels of job stress for female and male, respectively. Women had higher emotional exhaustion scores, while men were more likely to have low levels of job satisfaction. The multivariate analysis showed that factors independently associated with psychological morbidity, burnout, high levels of job stress and low levels of job satisfaction were generally similar for women and men. These findings increase our understanding of gender differences in psychological morbidity, burnout, job stress, and job satisfaction among neurologists. As more women join the medical profession, these differences may be useful in designing medical training and practice.